Towards the revitalisation of the Kromboom Parkway through the rehabilitation of the Kromboom River - Omar, Nicolas N (School of Architecture, Planning and Geomatics, 2014)
The system of public open space in South Africa is underperforming in relation to the natural assets this country possesses. After analysing the different aspects of the existing framework plans for the central metropolitan open space system, I was fascinated by the concept of linkage as vital to success. The Kromboom Parkway has always interested me because of its enormous potential, yet poor accessibility. By combining the the study of rivers with the open space framework and the concept of green corridors the idea of a redesign of the Kromboom Parkway came about. The analysis of the Public open space system at the larger scale puts the Kromboom Parkway into perspective, and it is a vital link. In fact without in the concept of a green corridor from False Bay to Table Bay is without a foundation, because the link from north to south would be broken. The Kromboom River is integral to the entire Kromboom Parkway pedestrian route. The Kromboom River itself is in need of erosion alleviation and some natural habitat construction to promote animal and plant life. In some cases the Kromboom River would be better off without the concrete canal. Proposing a design for the Kromboom Parkway requires an understanding of pedestrians and their needs and dislikes, the disabled and how to make spaces accessible to them and children and how they interact with space. Combine all these factors into a set of guidelines and the design starts to take shape.